THE ROLE OF AI MODELS IN VIRTUAL EDUCATION - Usman Arif, (Spectrum of Engineering Sciences, 2025)
The Artificial Intelligence is transforming the online education by digital revolution in designing course curriculum in AI Tools of Grammarly, Quill bot, Turnitin, Stealth writer, Chat GPT, Linked In, Canva Pro, Chegg, MS Office, Write Sonic, Course Hero, Scribd. The online education will be transformed by monolithic effects of Chat GPT for future designs like websites can read words and convert them into stories, ideas can develop themes, sketches can be transformed into pictures and voice leads can generate AI samples of mental schemas. The AI has certain limitations of what it does is asked for rather what Humans mean like facial recognition systems can search individuals globally by human pictures but human instincts of fear, love, hate needs to be measured by intelligent AI. The SLAs service level agreements for resources of digital libraries, e books and course materials of discussion panels in AI are the contracts provided by teachers for expected education quality for service based, student based and internal designs of education through generative AI. The Data Science for statistical analysis and computer architecture machine language ML are transforming virtual education in accuracy, speed , reliability and scalability . The KPIs are the performance metrics for quality standards, lectures for designing content management systems for course curriculum in learning depth, feed backs by use of generative AI. The AI tools of dash boards for updating records , data visualization track for narratives used by educational leaders for developing insights of students for improvements and opportunities . The AI can measure the qualitative learning data through survey methodology by questionnaire ,online tests applied to vast number of students by interview for AI models of teaching .The AI test scores will measure the student abilities of being intelligent , hard working, IQ, openness , agreeableness and efficiency